The Effectiveness of Corn Starch Addition on the Dimensional Stability of Irreversible Hydrocolloid Impressions - Kadek Dwi Dessy Sapitri; Ni Kadek Sugianitri; Kadek Ayu Wirayuni (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Dental impression materials are broadly classified into elastic and non-elastic types. One of the most commonly used elastic impression materials is irreversible hydrocolloid, which possesses several important properties, including ease of manipulation, patient comfort during intraoral application, the ability to reproduce fine surface details accurately, and hydrophilicity that facilitates adaptation to moist oral tissues. However, in clinical practice, impression procedures cannot always be carried out immediately in accordance with established protocols due to various factors. As a result, dimensional changes may occur if the impressions are not stored properly. These changes are primarily attributed to the inherent properties of irreversible hydrocolloid, namely imbibition (water absorption) and syneresis (water loss). One strategy to enhance the efficiency of irreversible hydrocolloid utilization is the incorporation of corn starch (Zea mays), which contains amylose and amylopectin. These components are capable of absorbing water and swelling, thereby potentially minimizing dimensional instability in diagnostic models derived from irreversible hydrocolloid impressions. The objective of this study was to evaluate the effect of adding corn starch (Zea mays) to irreversible hydrocolloid impression material on the dimensional stability of diagnostic models. Materials and Methods: This study employed a laboratory experimental design using a post-test only control group design, divided into three groups. Group I served as the control group, in which the samples were not given any addition of corn starch. Group II was the treatment group with the addition of corn starch and a resting time of 5 minutes. Group III was the treatment group with the addition of corn starch and a resting time of 10 minutes. The data obtained were then analyzed using ANOVA to determine differences among the groups. Results and Discussions: The results of the study and data analysis demonstrated that there was no statistically significant difference between the control group and the groups with the addition of corn starch in terms of dimensional stability changes of the alginate impression material. Incorporating starch in an optimal proportion can enhance the strength and hardness of the irreversible hydrocolloid gel. Conclusion: The addition of corn starch to irreversible hydrocolloid impressions has been shown to affect dimensional stability after storage for 5 and 10 minutes. Corn starch helps maintain the dimensional stability of the impressions at both time intervals, thereby improving the precision and accuracy of the resulting casts.